2022
DOI: 10.3390/ijerph192013447
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Needs of Rural Veterans: A Qualitative Evaluation of Whole Health Coaches’ Expanded Services and Support during COVID-19

Abstract: The purpose of this qualitative study was to explore perspectives of Whole Health (WH) coaches at the Veterans Health Administration (VHA) on meeting the needs of rural Veterans during the COVID-19 pandemic. The evaluation design employed a qualitative description approach, employing focus groups and in-depth interviews with a convenience sample of WH coaches across the VHA system. Fourteen coaches who work with rural Veterans participated in either one of three focus groups, individual interviews, or both. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Each VA network has had the leeway to implement Whole Health coaching differently across sites: coaches may be Veterans or other healthcare workers who have undergone specialized training and have provided goal-setting consultations through different modalities throughout the pandemic. 27,28 Coaching may assist with building organizational capacity, lower provider stress, and diffuse this innovation at the microsystem level (PACT team). Previous research indicates that Veterans benefitted from shortterm coaching, but desired more intensive and ongoing coaching programs for goal attainment, 29 requiring sufficient FTE allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Each VA network has had the leeway to implement Whole Health coaching differently across sites: coaches may be Veterans or other healthcare workers who have undergone specialized training and have provided goal-setting consultations through different modalities throughout the pandemic. 27,28 Coaching may assist with building organizational capacity, lower provider stress, and diffuse this innovation at the microsystem level (PACT team). Previous research indicates that Veterans benefitted from shortterm coaching, but desired more intensive and ongoing coaching programs for goal attainment, 29 requiring sufficient FTE allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Whole health coaches engage in exploring clients' feelings in an effort to identify factors, including social aspects (Hale-Gallardo et al, 2022), that might influence health behaviors, a key aspect of Pender's Health Promotion Model. When whole health coaches identify clients' strengths, they support the clients' self-efficacy, or can-do attitude, supported by previous research (Purcell et al, 2021;Nelson et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the personal and professional experience of the role of a whole health coach is limited. Whole health coaches working with veterans in rural settings during the COVID-19 pandemic (N=14) were interviewed and identified themes centered around leveraging technology, addressing social factors, redirecting self-care modes, and being flexible (Hale-Gallardo et al, 2022). Three health coaches were interviewed regarding their experiences in a novel, 12-week, whole person care intervention and validated participants' perception of the value of the program, including increased health awareness and motivation, goal setting and accountability, self-efficacy, individualized support, and coaching (Nelson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These changes greatly accelerate the loss of muscle mass and decline in physical function in older people, which are key characteristics of sarcopenia ( Cruz-Jentoft and Sayer, 2019 ). In addition, the COVID-19 pandemic has disrupted the way research is conducted, given the reduced chance to interact with participants in person and the increased reliance on digital technologies ( Hale-Gallardo et al, 2022 ). This has increased the risk of leaving behind those who lack digital literacy or are too unwell to use such tools ( Hale-Gallardo et al, 2022 ), such as older people with sarcopenia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the COVID-19 pandemic has disrupted the way research is conducted, given the reduced chance to interact with participants in person and the increased reliance on digital technologies ( Hale-Gallardo et al, 2022 ). This has increased the risk of leaving behind those who lack digital literacy or are too unwell to use such tools ( Hale-Gallardo et al, 2022 ), such as older people with sarcopenia. Moreover, studies have shown that people who have recovered from COVID-19 may have long-term symptoms that cannot be explained, known as “long COVID” ( Peter et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%